Unfriendly Fire: How the Tobacco Industry is Destroying the Future of Our Children - Bush, Andrew; Ferkol, Thomas; Valiulis, Algirdas; Mazur, Artur; Chkhaidze, Ivane; Maglakelidze, Tamaz; Sargsyan, Sergey; Boyajyan, Gevorg; Cirstea, Olga; Doan, Svitlana; Katilov, Oleksandr; Pokhylko, Valeriy; et al. (Acta medica Lituanica, 2021)
Tobacco has long been known to be one of the greatest causes of morbidity and mortality in the adults, but the effects on the foetus and young children, which are lifelong, have been less well appreciated. Developing from this are electronic nicotine delivery systems or vapes, promulgated as being less harmful than tobacco. Nicotine itself is toxic to the foetus, with permanent effects on lung structure and function. Most vapes contain nicotine, but they also contain many other compounds which are inhaled and for which there are no toxicity studies. They also contain known toxic substances, whose use is banned by European Union legislation. Accelerating numbers of young people are vaping, and this does not reflect an exchange of vapes for cigarettes. The acute toxicity of e-cigarettes is greater than that of tobacco, and includes acute lung injury, pulmonary haemorrhage and eosinophilic and lipoid pneumonia. Given the worse acute toxicity, it should be impossible to be complacent about medium and long term effects of vaping. Laboratory studies have demonstrated changes in lung proteomics and the innate immune system with vaping, some but not all of which overlap with tobacco. It would be wrong to consider vapes as a weaker form of tobacco, they have their own toxicity. Children and young people are being targeted by the vaping industry (which is largely the same as the tobacco industry), including on-line, and unless an efficient legislative program is put in place, a whole new generation of nicotine addicts will result.